Innovative Strength‐Based Care in Child and Adolescent Inpatient Psychiatry. Issue 3 (23rd August 2016) - Sams, Deanna P.; Garrison, David; Bartlett, Joanne
Abstract : PROBLEM: Child and adolescent psychiatric units serve the highest risk, most vulnerable populations in the mental health delivery system. This article describes the integration of a strength‐based approach with a traditional, medical model of psychiatric care on an acute inpatient unit. A strength‐based framework allows for increased focus on exploring patients' goals, strengths, relationships, skills, and family communication within the hospital setting. METHODS: The process of integration of strength‐based care is described, followed by discussion of the implementation and evaluation of interventions, including mindfulness, family movie, narrative, and animal‐assisted therapies. FINDINGS: Innovative interventions led to improvement in patient symptoms, unit culture, and patient, family, and staff satisfaction. CONCLUSION: A strong emphasis on strength‐based, multidisciplinary treatment has enhanced patient care, as the goals of acute inpatient admission are broadened to include more than diagnosis and medication management.